The role of social media in forming and modifying public opinion among Syrian university students ((Field study on students of the Faculty of Political Science and the Faculty of Mass Communication at Damascus University(( - حلاق, بطرس; حجازي , جمعة; سليمان, دارين (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The study aimed to know the opinions of students of the Faculty of Political Science and the Faculty of Media at Damascus University on the influence of well-known social media sites on forming, directing and modifying public opinion. For this purpose, the researcher designed a questionnaire to be applied to the study sample of (48) students. After conducting the appropriate statistical treatments, the results of the study showed that Facebook is the first in terms of the degree of influence on public opinion among the members of the study sample, followed by Twitter, and that social networking sites greatly affect the formation of public opinion, especially in the cultural field. There are statistically significant differences in the students ’opinions due to the study variables (gender - specialization).